2019
DOI: 10.3389/fneur.2019.01127
|View full text |Cite
|
Sign up to set email alerts
|

Dreams and Nightmares in Patients With Obstructive Sleep Apnea: A Review

Abstract: Obstructive sleep apnea (OSA) can present with or provoke various psychological symptoms. In this article, we critically review studies that have examined dreams, dream recall, and dream content in patients with OSA. Obstructive events induce recurrent sleep fragmentation and intermittent desaturations in patients with OSA, which may trigger different parasomnias, including nightmares. Contradictory results have been reported concerning dreams in patients with OSA; while some investigators have reported less d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“… 82 One explanation could be that it depends on the OSA being REM-stage specific or not. 83 OSA is relevant during the pandemic as people at high risk for OSA were more likely to contract COVID-19, to be hospitalized or receive intensive unit care treatment. 73 …”
Section: Discussionmentioning
confidence: 99%
“… 82 One explanation could be that it depends on the OSA being REM-stage specific or not. 83 OSA is relevant during the pandemic as people at high risk for OSA were more likely to contract COVID-19, to be hospitalized or receive intensive unit care treatment. 73 …”
Section: Discussionmentioning
confidence: 99%
“…Parasomnias are dissociated sleep states which are partial arousals during transitions between wakefulness, NREM sleep, REM sleep, and their combinations ( Howell, 2012 ). Multiple studies have shown that OSAHS is associated with parasomnias, including nightmares ( BaHammam and Almeneessier, 2019 ), RBD, sleepwalking, and sleep terrors ( Guilleminault et al, 2003 ; Haupt et al, 2013 ). A study of 84 children with recurrent or long-term sleepwalking showed that 58% had OSAHS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with OSAHS often present at sleep centers because of nightmares ( BaHammam and Almeneessier, 2019 ) and other parasomnias. Some symptoms of parasomnias are secondary to OSAHS ( Goyal et al, 2018 ), and when OSAHS is effectively treated, the symptoms of parasomnia are also relieved ( Carrasco et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, awakenings from obstructive events often occur with sympathetic nervous system activation, with associated symptoms of racing heart, shortness of breath, and anxiety, all of which could worsen the experience of a nightmare [47]. OSA has been associated with nightmares even in individuals without PTSD, often with content related to suffocation, choking, drowning, strangulation, burial, and death [48][49][50][51]. A study of patients with OSA who slept in a laboratory before and after starting continuous positive airway pressure (CPAP) were awakened after the beginning of every REM period for dream reports.…”
Section: The Osa and Ptsd Overlapmentioning
confidence: 99%